The Tradition of Epirus in the Late Byzantine Architecture of North Macedonia - Zavorina, Maria L. (Actual Problems of Theory and History of Art, 2021)
The article examines the specificity of the assimilation of the architectural tradition of Epirus in the regional centers of North Macedonia — Ohrid and Prilep, as well as in the territories under the Serbian rule, north of the Ohrid–Prilep–Stip borderline. Stylistic and comparative Analysis of the churches of Ohrid and Prilep in the context of the architectural processes of the 13th–early 14th centuries shows that the presence of the Epirote school here is not limited to the reproduction of individual elements, but is guided by the main trends of the Palaeologan period. The lack of pronounced local specificity gives reason to consider the Late Byzantine architecture of North Macedonia in the second half of the 13th — first half of the 14th century as a consistent continuation of the tradition of Epirus outside the Despotate at the stage of the formation of Palaeologan style.This study is based on the research, supported by the Program of Fundamental Research of the Russian Academy of Architecture and Construction Sciences and of the Ministry of Construction, Housing and Utilities of the Russian Federation – 2021, research project 1.1.1.2.
Keywords: Byzantine architecture; Epirus; North Macedonia; Ohrid; Prilep